Appraisal of Ethno-veterinary practices used for different livestock ailments in rural and peri-urban areas of Purba Bardhaman, West Bengal, India - Pal, Suvendu; Mitra, Pritish; Dey, Somen; Ganguly, Arindam; Mandal, Asish (Ethnobotany Research and Applications, 2024)
Background: Plant species contribute fodder and forage to livestock and are also used traditionally as ethnomedicines in curing various health disorders. High cost and massive side effects of conventional drugs, often promotes indigenous people to depend on traditional phytomedicines. This study is an attempt to document the indigenous knowledge of ethnoveterinary plants and practices by the people of Purba Bardhaman District, West Bengal, India. Methods: 135 informants from different rural and peri-urban areas were interviewed through a standardized questionnaire throughout the year, 2023. The collected ethnoveterinary data was analysed through frequency of citation (FC), relative frequency of citation (RFC), use value (UV), number of use (NU) to determine the level of knowledge and use of plant species by local communities against various diseases. Results: 38 plant species have been recorded which belong to 37 genera and 27 families. Diarrhoea, chronic wound, eye spot, mastitis, respiratory problem, and worm infection are found to be the most common diseases. The highest FC (77), RFC (0.57) and UV (0.85) were contributed by Moringa oleifera against these diseases. The practices in rural and peri-urban areas are more or less same. In most cases the required plants are collected from the field in wild conditions although some plants are cultivated in rural areas. Due to over-exploitation, ignorance, over grazing these plants are needed to be conserved. Conclusions: The work provides a list of ethnoveterinary plants for livestock medicine preparation. The plants with high value of ethnobotanical indices can be potential sources of novel drugs through modern phytomedicinal approaches. Keywords: Ethnoveterinary medicine, Indigenous knowledge, Livestock care, Quantitative ethno-veterinary.